Effects of biochar addition on nitrous oxide emission during soil freeze–thaw cycles - Yang, Zhihan; She, Ruihuan; Hu, Lanfang; Yu, Yongxiang; Yao, Huaiying (Frontiers in Microbiology, 2022)
Abstract Biochar applied to soil can reduce nitrous oxide (N2O) emissions produced by freeze‒thaw processes. Nonetheless, how biochar modification affects N2O emissions during freeze‒thaw cycles is not completely clear. In our research, during freeze‒thaw cycles, microcosm experiments were conducted to investigate the effects of maize straw biochar (MB) or rice straw biochar (RB) addition on soil N2O emissions under different water conditions. The N2O emissions peaked at the initial stage of thawing in all the soils, and the total N2O emissions were considerably greater in the flooded soils than in the nonflooded soils. Compared with the soils without biochar addition, RB and MB amendments inhibited N2O emissions by 69% and 67%, respectively. Moreover, after biochar addition, the abundance of AOB amoA genes decreased by 9% to 13%. Biochar addition significantly decreased the content of microbial biomass nitrogen (MBN) in flooded soil during thawing, which was significantly correlated with N2O emissions and nitrification and denitrification communities. The PLS-PM further revealed that biochar can inhibit the production and emission of soil N2O by reducing soil MBN during soil thawing. In addition, soil moisture directly significantly affects N2O emissions and indirectly affects N2O emissions through its influence on soil physicochemical properties. Our results revealed the important function of biochar in decreasing the emission of N2O in flooded soil during freeze‒thaw cycles.